Efectos de la musicoterapia en la salud mental: Un análisis documental sistemático de los años del 2009 al 2024 (2024)
In the development of systematic document analysis, the focus was on exploring the effects of music therapy on the mental health of patients with various pathologies in different age groups, using data from the last fifteen years. During this process, a matrix was constructed as a control for the investigations, classifying the information into three main categories and twelve specific subcategories. The study is based on a qualitative approach that aims to understand the experiences and perspectives of the involved population. It was carried out with a descriptive methodology that sought to capture and analyze in detail the studied phenomena